Prospective physical fitness status and development of cardiometabolic risk in children according to body fat and lifestyle behaviours: The IDEFICS study. Issue 11 (18th May 2021) - Santaliestra‐Pasías, Alba M.; Moreno, Luis A.; Gracia‐Marco, Luis; Buck, Christoph; Ahrens, Wolfgang; De Henauw, Stefaan; Hebestreit, Antje; Kourides, Yiannis; Lauria, Fabio; Lissner, Lauren; Molnar, Denes; Veidebaum, Toomas; et al.
Summary: Background: Elevated cardiometabolic risk (CMR) is an important factor for cardiovascular diseases later in life while physical fitness seems to decrease CMR. Objective: Thus, the aim of the present study is to assess the association between muscular fitness (MF) and cardiorespiratory fitness (CRF) on CMR in European children, both cross‐sectional and longitudinally. Methods: A total of 289 children (49.5% males) from eight European countries, aged 6 to 9, with longitudinal information on blood pressure, triglycerides, total cholesterol, HDL‐cholesterol, homoeostasis model assessment, body mass index, data on fitness level, objectively measured physical activity (PA), diet quality, and total screen time were included. A CMR score was calculated and dichotomized. MF and CRF were also dichotomized. Cross‐sectional and longitudinal multilevel logistic regressions adjusting for lifestyle behaviours were performed. Results: Reaching a high level of MF during childhood as well as remaining in that level over‐time were associated with an 82% and 62% lower probability of high CMR at follow‐up, respectively. Also, children who became top CRF over time, showed a 77% lower probability ( P  < 0.05) of being in the highest CMR quartile at follow‐up, independently of sociodemographic and lifestyle indicators. Conclusions: A high MF at early childhood and during childhood reduces the odds of having CMR. Same occurs with the improvement of CRF during childhood. These findings highlight the importance of enhancing fitness to avoid CMR already in children.